Influence of waves on the three-dimensional distribution of plastic in the ocean. (February 2023) - Bajon, Raphaël; Huck, Thierry; Grima, Nicolas; Maes, Christophe; Blanke, Bruno; Richon, Camille; Couvelard, Xavier
Abstract: The world's oceans are facing plastic pollution, 80 % of which of terrestrial origin flowing from the mismanaged waste of coastal populations and from river discharge. To study the fate of this pollution, the three-dimensional trajectories of neutral plastic particles continuously released for 24 years according to realistic source scenarios are computed using currents from a global ocean-wave coupled model at 1 4 ∘ resolution and from a reference ocean-only model. These Lagrangian simulations show that neutral particles accumulate at the surface in the subtropical convergence zones from where they penetrate to about 250 m depth and strongly disperse over 40 ∘ of latitude. About 5.3 % of the particles remain at the surface with the wave-coupled model currents, whereas only 2 % for the uncoupled model, with some modulation in the location of the convergence zones. Increased surface retention results from upward vertical velocities induced by widespread divergence of waves-induced Stokes transport in the surface layers. Highlights: Land-based scenario considers plastic waste from coastal populations or brought by rivers. 3D global dispersion of neutral 'plastic' particles in the global ocean Coupled ocean-wave dynamics increase the surface retention of plastic by a factor of Shapes of the concentrated plastic areas change when coupling with waves. Ocean-wave coupling induces upward velocities below subtropical convergence zones.